VITICULTURE AND FRUIT GROWING IMPORTANCE IN THE NATIONAL ECONOMY - Matmuratova Gulnoza Bahtiyarovna (Bright Mind Publishing, 2025)
Horticulture is one of the main sectors that determines the economy of the Republic of Uzbekistan and brings a lot of income. Without developing this industry on a scientific basis, it is impossible to satisfy the demand for fruit products of the population and our industry. Therefore, it is necessary to thoroughly study agricultural sectors, including horticulture, to find out what problems have occurred and to find a positive solution to them.
Keywords: Fruit, viticulture, horticulture, agriculture, vineyard